Drug Delivery to the Human and Mouse Uterus Using Immunoliposome Targeted to the Oxytocin Receptor. Issue 4 (December 2017) - Paul, J.W.; Hua, S.; Ilicic, M.; Tolosa, J.M.; Butler, T.; Robertson, S.; Smith, R.
Abstract : ( Am J Obstet Gynecol. 2017;216(3):283.e1–283.e14) There is a need for pharmacotherapy during preterm labor, postpartum hemorrhage and other obstetric complications that is safe, effective and specifically targets uterine myocytes with minimal side effects. One emerging mode to deliver agents to specific tissues is targeted liposomes, which are artificial vesicles composed of ≥1 phospholipid bilayers. This study examined the possibility of developing a method for targeting uterine myometrial tissue with therapeutic agents using an immunoliposome platform.